The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1177/0269881198012003031
|View full text |Cite
|
Sign up to set email alerts
|

Selective serotonin reuptake inhibitors in affective disorders -II. Efficacy and quality of life

Abstract: Since their introduction, the selective serotonin reuptake inhibitors (SSRIs) have become one of the most widely used classes of medication in psychiatry. Their popularity is based on apparent efficacy over a wide range of disorders and a favorable side-effect profile. However, as with any psychotropic medication, considerable data are required to define where a drug works and where it does not. There is now a wealth of evidence demonstrating that SSRIs may differ in their efficacy profiles in certain depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 145 publications
(196 reference statements)
2
21
0
Order By: Relevance
“…Both beneficial (Levkovitz et al, 2002;Harmer et al, 2004;Zobel et al, 2004) and detrimental (Masand and Gupta, 1999;Schmitt et al, 2001;Joss et al, 2003) effects have been reported. In part, this may be due to the differing pharmacological, and hence specific cognitive effects, or individual SSRIs Goodnick and Goldstein, 1998). It was not possible to pursue this in the current study because of the small numbers involved.…”
Section: Discussionmentioning
confidence: 96%
“…Both beneficial (Levkovitz et al, 2002;Harmer et al, 2004;Zobel et al, 2004) and detrimental (Masand and Gupta, 1999;Schmitt et al, 2001;Joss et al, 2003) effects have been reported. In part, this may be due to the differing pharmacological, and hence specific cognitive effects, or individual SSRIs Goodnick and Goldstein, 1998). It was not possible to pursue this in the current study because of the small numbers involved.…”
Section: Discussionmentioning
confidence: 96%
“…Our findings might have some relevance to approaches relying upon the modification of serotonergic functions in the brain for treating disorders such as e.g., depression, anxiety, or post-traumatic stress. Concerning depression, for instance, selective serotonin reuptake inhibitors (SSRI) have the best safety record among the different therapeutic options (van Laar et al, 2002), but there is a literature reporting on possible SSRI-related memory problems (Goodnick and Goldstein, 1998;Joss et al, 2003;Wadsworth et al, 2005). Although these memory problems could be related to various confounding factors (subject's history, age, existence of age-related cognitive dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies have concluded that SSRIs have fewer adverse effects (Nutt, 2003;Hindmarch, 1995), both in the short-and long-term (Cassano and Fava, 2004), are relatively free from cognitive and psychomotor effects (Hindmarch 1995) and do not impair driving performance (Hale, 1994). The side-effect profiles of individual SSRIs do, of course, vary Goodnick and Goldstein, 1998), as do their specific effects on cognitive function (Oxman et al, 1996). In this study fluoxetine and paroxetine were most commonly used, but individual analyses were not possible because of small numbers.…”
Section: Discussionmentioning
confidence: 99%